STUDI KOMPARASI REGULASI DAN IMPLEMENTASI PERLINDUNGAN SAKSI DAN KORBAN NEGARA INDONESIA DAN AMERIKA SERIKAT - Sitepu, Immanuel Yefri Aronta; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to conduct a comparative study between regulations and implementation of witness and victim protection in Indonesia and the United States. The existing problem phenomenon shows that witnesses and victims of crime often have their safety and security threatened, requiring a protection system that is effective and responsive to their needs. This research uses empirical juridical methods, combining juridical legal analysis with empirical data obtained from direct observation and related sources. It was found that in Indonesia, the protection of witnesses and crime victims is integrated in legal frameworks such as the Criminal Procedure Code, Criminal Code, and Law no. 13 of 2006. The Witness and Victim Protection Agency (LPSK) has an important role in implementing various protection mechanisms. Meanwhile in the United States, witness protection is regulated in the Witness Protection Act 1984 with the Bureau of Prisons and the U.S. The Marshals Service plays a vital role in supervising and protecting witnesses. The results show important differences in approaches to witness and victim protection between the two countries. The United States offers an intensive protection system through a structured witness protection program, while Indonesia emphasizes a broad legal framework with implementation based on independent institutions.Keywords: Witness and victim protection, regulations, implementation.